1994
DOI: 10.1080/03079459408418971
|View full text |Cite
|
Sign up to set email alerts
|

Maduramicin and tiamulin compatibility in broiler chickens

Abstract: A total of 480 1-day-old Hybro broiler chickens were divided into five treatment groups (A: unmedicated control, B: maduramicin, C: maduramicin + tiamulin, D: monensin + tiamulin and E: tiamulin) to study the effect on performance parameters, organ weights, blood haematology and biochemistry, and histopathology of liver and selected striated muscles, when maduramicin at 5 parts/10(6) and monensin at 100 parts/10(6) were included in feed in starter and grower periods, and tiamulin 9 in water at 270 parts/10(6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Animal protein, furazolidone, tiamulin, macrolide antibiotics, and neomycin-permethrin can potentiate ionophore toxicity in various species of animals. 2,3,5,35 Samples of suspect DDG contained residues of the antibiotics erythromycin and clarithromycin and related analogs. Erythromycin and clarithromycin belong to the macrolide class of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Animal protein, furazolidone, tiamulin, macrolide antibiotics, and neomycin-permethrin can potentiate ionophore toxicity in various species of animals. 2,3,5,35 Samples of suspect DDG contained residues of the antibiotics erythromycin and clarithromycin and related analogs. Erythromycin and clarithromycin belong to the macrolide class of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically important interactions between ionophore anticoccidials and the antibiotic tiamulin (and other antibiotics) are well-known phenomena in chickens, turkeys and other species (EFSA, 2004). The severity of adverse effects varies depending on the ionophore itself, reaching from increased mortality to only transient performance depression (Badiola, et al, 1994;Schuhmacher, et al, 2006). Badiola (1994) studied the compatibility of maduramicin ammonium (5 mg/kg feed) with tiamulin (270 mg/L drinking water from day 28 to 31) for 52 days.…”
Section: Incompatibilities and Interactionsmentioning
confidence: 99%
“…The severity of adverse effects varies depending on the ionophore itself, reaching from increased mortality to only transient performance depression (Badiola, et al, 1994;Schuhmacher, et al, 2006). Badiola (1994) studied the compatibility of maduramicin ammonium (5 mg/kg feed) with tiamulin (270 mg/L drinking water from day 28 to 31) for 52 days. As the only adverse effect of the simultaneous administration, the authors found a transient depression of feed intake and growth during and following the 14-day period of tiamulin administration.…”
Section: Incompatibilities and Interactionsmentioning
confidence: 99%
“…Clinically important interactions between ionophore anticoccidials and the antibiotic tiamulin (and other antibiotics) are well-known phenomena in chickens, turkeys and other species (EFSA, 2004). In assessing the results of a study of Badiola et al (1994), the FEEDAP Panel was not in a position to establish the full compatibility of Maα and tiamulin in chickens for fattening (EFSA FEEDAP Panel, 2011b). The same interaction is consequently assumed for Maα in turkeys for fattening.…”
Section: Incompatibilities and Interactionsmentioning
confidence: 99%
“…In assessing the results of a study of Badiola et al (1994), the FEEDAP Panel was not in a position to establish the full compatibility of Maα and tiamulin in chickens for fattening (EFSA FEEDAP Panel, 2011b). The same interaction is consequently assumed for Maα in turkeys for fattening.…”
Section: Incompatibilities and Interactionsmentioning
confidence: 99%